A Vision of K-12 Computer Science Education for 2030: Exploring goals, perspectives, and challenges. - Tissenbaum, Mike; Ottenbreit-Leftwich, Anne; Guzdial, Mark (Communications of the ACM, 2020)
The article discusses the 2030 education goals, perspectives, and challenges for K-12 computer science (cs) education. It reports that most states in the U.S. are working towards computer science requirements for grades K-8, with elective courses available for 9-12. It warns that computer science classes must expand beyond just coding to appeal to a wide array of student, regardless of gender or race. Topics include computer literacy, the impact of changing computer technologies on society, and making cs a part of an interdisciplinary approach to education.